2015
DOI: 10.1007/s00774-014-0646-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of teriparatide to alleviate pain and to prevent vertebral collapse after fresh osteoporotic vertebral fracture

Abstract: Vertebral fracture is often seen in osteoporotic patients. Teriparatide is expected to promote bone union. Therefore, we evaluated the action of vertebral collapse prevention by administering teriparatide to vertebral fracture patients. Thirty-four patients with fresh vertebral fracture (48 vertebrae) participated in this study. They were administered either teriparatide (daily 20 µg/day or weekly 56.5 µg/week) or risedronate (17.5 mg/week): ten patients (20 vertebrae) received teriparatide daily (Daily group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…[283134] In spine fractures, teriparatide showed various effects on pain relief per weeks after trauma. [3536] Physical performances including Timed Up-and-Go (TUG) test and time to mobilization were significantly improved in the teriparatide group with fractures of the pelvis and pertrochanteric femur[29303133] but, other function scores such as disabilities of the arm, shoulder, and hand (DASH) and grip strength revealed no differences in fractures of proximal humerus and distal radius after teriparatide injection. [2834]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[283134] In spine fractures, teriparatide showed various effects on pain relief per weeks after trauma. [3536] Physical performances including Timed Up-and-Go (TUG) test and time to mobilization were significantly improved in the teriparatide group with fractures of the pelvis and pertrochanteric femur[29303133] but, other function scores such as disabilities of the arm, shoulder, and hand (DASH) and grip strength revealed no differences in fractures of proximal humerus and distal radius after teriparatide injection. [2834]…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the other study showed significant reduction of pain numerical scale within 8 or 12 weeks after trauma. [36]…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we applied 2 pain-related behavioral tests-the plantar test (paw flick test, a test observing avoidance of heat stimulation) and the von Frey test (a test to evaluate hyperalgesia by observing avoidance of mechanical stimulation)-to OVX rats to experimentally evaluate whether or not TPTD exerts an antinociceptive effect on this osteoporotic animal model, as has been observed in several clinical reports [15][16][17][18][19][20][21][22][23][24][25] . The plantar test showed that the withdrawal latency was gradually reduced in the OVX rats during the observation period compared with the Sham-vehicle group, confirming thermal hyperalgesia caused by OVX 8,10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present case series, the major symptoms of SIFs, which were low back or buttock pain, rapidly decreased after 1 month of treatment with TPTD. Several studies have demonstrated low back pain from vertebral fracture in patients with osteoporosis to be reduced with TPTD treatment (14)(15)(16)(17)(18). A meta-analysis showed that TPTD significantly reduced the risk of moderate or severe back pain compared to placebo, alendronate, or hormone replacement therapy in the patients with osteoporosis (15).…”
Section: Discussionmentioning
confidence: 99%